2014
DOI: 10.1038/srep06983
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Free Counter Electrode Comprised of Metal-Organic-Framework (MOF)-Derived Cobalt Sulfide Nanoparticles for Efficient Dye-Sensitized Solar Cells (DSSCs)

Abstract: We fabricated a highly efficient (with a solar-to-electricity conversion efficiency (η) of 8.1%) Pt-free dye-sensitized solar cell (DSSC). The counter electrode was made of cobalt sulfide (CoS) nanoparticles synthesized via surfactant-assisted preparation of a metal organic framework, ZIF-67, with controllable particle sizes (50 to 320 nm) and subsequent oxidation and sulfide conversion. In contrast to conventional Pt counter electrodes, the synthesized CoS nanoparticles exhibited higher external surface areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(67 citation statements)
references
References 44 publications
(50 reference statements)
2
64
0
Order By: Relevance
“…Through removing metallici ons in MOFs by various methods, ar obust and highly porousc arbon backbone can be achieved.I n2 016, Sun et al first reported preparing porous carbon spheres as DSSC counter electrodes by thermal carbonization of ZIF-8 in argon at elevated temperatures. [122] More recently,C ui et al reported the synthesis of CoS 2 -embedded carbonn anocages through directly sulfurizing ZIF-67 ( Figure 9). The optimal sample gave ag ood electrochemical performance with aP CE of 7.32 %, which wasc omparablet ot he performance of the platinum electrode.…”
Section: Mof-derived Nanostructuresasc Ounter Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through removing metallici ons in MOFs by various methods, ar obust and highly porousc arbon backbone can be achieved.I n2 016, Sun et al first reported preparing porous carbon spheres as DSSC counter electrodes by thermal carbonization of ZIF-8 in argon at elevated temperatures. [122] More recently,C ui et al reported the synthesis of CoS 2 -embedded carbonn anocages through directly sulfurizing ZIF-67 ( Figure 9). The optimal sample gave ag ood electrochemical performance with aP CE of 7.32 %, which wasc omparablet ot he performance of the platinum electrode.…”
Section: Mof-derived Nanostructuresasc Ounter Electrodesmentioning
confidence: 99%
“…Some heavy-metal ions, such as iron and zinc, are essential nutrients for human health at very low concentrations.T hey functione ither as catalysts in metalloproteins or as cofactors/activators of reactions involving enzymes. [122,124] Heavy-metal-ion pollution has become as erious environmental issue owing to the rapid development of modern industry.T herea re many types of heavy-metal-ion pollution in industrial wastewaters from battery manufacturing, smelting, tanneries, metal plating, ands of orth. However, even at relatively low concentrations, heavy-metal ions tend to form complexes with biological molecules containing nitrogen, sulfur,a nd oxygen, which can induce structural changes and bond breakage of biological molecules, and therefore, may affect the function of human tissues and organs,s uch as central nervous systems, kidneys,l ivers, skin, bones, or teeth.…”
Section: Mofs For Environmental Cleaning Applicationsmentioning
confidence: 99%
“…The PCE of the DSSCs with CoS ANRA counter electrodes reached 7.67%, and this efficiency was close to that of the DSSC with Pt counter electrode (7.70%). Recently, Hsu et al synthesized CoS nanoparticles by CTAB-assisted preparation of a metal organic framework, ZIF-67, and subsequent oxidation and sulfide conversion to CoS [17]. The generated CoS nanoparticles was used as counter electrode for DSSCs, leading to an improved efficiency of 8.1%.…”
mentioning
confidence: 99%
“…However, the J SC value of ACs is further improved by extraction of nano-Si with ACs surface; (ii) Open-circuit potential: Under same experimental conditions, nano-Si@ACs CE depicts higher V OC (0.76 V) value than that of ACs (0.73 V) and conventional Pt (0.74 V) CEs of DSSCs. Indeed, V OC is the difference of Fermi level of semiconducting material and potential energy of redox potential in electrolyte, which is influenced by instinct material properties of the CEs42. Therefore, higher V OC for nano-Si@ACs is the result of its higher J SC value; and (iii) Fill factor: In fact, FF is closely associated to charge transfer resistance at CE of DSSCs.…”
Section: Resultsmentioning
confidence: 99%